Corporate Ethics at CV NCK Collection: The Ineffectiveness of Human Resource Management Policies - Nurul Mardhiah Sitio; Imas Farida (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Corporate ethics in the company is very important because it becomes a reference for making policies in the company. CV. NCK Collection is a branch company in Banjar City. In carrying out its business activities, the CV carries out many policies that are considered ineffective, especially in its human resource management policies. This ineffective policy concerns layoffs, recruitment, a system of salaries and overtime wages, employee demotion and human rights issues. The purpose of this study is to discuss the ineffectiveness of the policies made by CV. NCK Collection with corporate ethics that should be noticed. The research method used in this research is a qualitative method with primary and secondary data sources. Primary data sources were obtained through unstructured interviews and secondary sources were obtained through literature studies. The results of this study found that the CV. NCK Collection was proven to experience policy ineffectiveness, especially in human resource management policies.